Strategic Information Warfare A New Face of War - Molander, Roger C. (RAND Corporation, 1996)
Future U.S. national security strategy is likely to be profoundly affected by the ongoing, rapid evolution of cyberspace--the global information infrastructure--and in particular by the growing dependence of the U.S. military and other national institutions and infrastructures on potentially vulnerable elements of the U.S. national information infrastructure. To examine these effects, the authors conducted a series of exercises employing a methodology known as the Day After ... in which participants are presented with an information warfare crisis scenario and asked to advise the president on possible responses. Participants included senior national security community members and representatives from security-related telecommunications and information-systems industries. The report synthesizes the exercise results and presents the instructions from the exercise materials in their entirety.